História oral e autobiografia no teatro documentário - Elise Tuma Vieira dos Santos (2013)
This dissertation intends to investigate Documentary Theatre, itsconcept, origin context and, more specifically, the use it makes of oralhistory and autobiography. The study starts with a bibliographic surveywhich emphasizes North American and British publications about thetheme, maps certain aspects that are usually present in this kind of theatre, and focuses in two main ones (autobiography and oral history), giving significant examples of them. It discusses the importance of rescuing oral narratives in contemporary life; the dialogue established between theatre artists and a chosen social group as a way of stimulating, producing and using oral history in documentary theatre; the presence of autobiography in this kind of theatre as a non-individualistic way of expressing subjectivity in contemporary society and documentary theatre as an artistic way of expressing social memory.